Perancangan Biosand Filtration untuk Kualitas Air Berdasarkan Tekanan Pompa dari Limbah Industri Kelapa Sawit: Biosand Filtration Design for Water Quality Measurement Based on Pump Pressure from Palm Oil Industry Waste - ARJUNA NENI TRIANA; MEGA ARIANA (Jurnal Teknologi Lingkungan, 2023)
ABSTRACT The Noman River, the main river that crosses Muaraenim Regency, South Sumatra Province, has been polluted by the liquid waste from the palm oil industry. This study aimed to create a filter device for treating the polluted water waste. This was achieved by designing a pump pressure setting on the filter device with various filter media arrangements. The method used was descriptive, presenting data in graphs and tables. The research and tool design to create a filter device for treating the polluted water waste process involved several stages: tool planning, manufacture and assembly, testing, observation, calculation, and laboratory analysis. The observed parameters included pump pressure, regulated using a pressure gauge to determine water quality before and after filtering. The parameters observed were turbidity, color, pH, suspended solids (TSS), BOD, COD, oil, and grease. The study results indicate that biosand filtration, using different pressures, can treat river water contaminated with waste from the palm oil industry and produce clean water. The initial color of the water before filtering was measured at 230 TCU. After filtering, the color value decreased at each pressure level. Pressure I had a color value of 164 TCU, higher than the 153 TCU obtained at pressure II. The BOD analysis showed a decrease from 2.43 mg/L to 1.86 mg/L at pressure I before filtering. After filtering, the initial total suspended solids (TSS) level was 39.7 mg/L, which decreased to 26.79 mg/L at pressure I and 26.40 mg/L at pressure II. The oil and fat content analysis before filtering showed a concentration of 700 µg/L, which decreased to 501 µg/L at pressure I and 516 µg/L at pressure II after filtering. ABSTRAK Sungai Noman, sebagai sungai utama, melewati Kabupaten Muaraenim, Propinsi Sumatera Selatan, telah mengalami pencemaran dari limbah cair industri kelapa sawit. Penelitian bertujuan untuk membuat alat penyaring dari limbah air tercemar dengan desain pengaturan tekanan pompa pada alat penyaring dengan berbagai susunan media filter. Metode deskriptif digunakan dalam penelitian ini dilengkapi dengan data tabel dan grafik. Tahap analisis serta penyediaan alat melewati beragam tahap seperti perencanaan alat, pembuatan dan perakitan alat, pengujian alat, pengamatan, perhitungan, dan analisis laboratorium. Parameter yang diamati yaitu tekanan pompa yang diatur melalui pressure gauge, untuk mendapatkan kualitas air sebelum dan sesudah penyaringan. Parameter yang diamati nilai kekeruhan, warna, pH, total suspended solid (TSS), chemical oxygen demand (COD), biological oxygen demand (BOD), minyak, serta lemak. Hasil penelitian menunjukkan bahwa biosand filtration dengan mengunakan tekanan yang berbeda mampu untuk mengolah air sungai dari limbah industri kelapa sawit menjadi air bersih. Warna air sebelum penyaringan sebesar 230 TCU dan setelah dilakukan penyaringan mengalami penurunan nilai warna pada masing-masing tekanan, tekanan I yaitu 164 TCU memiliki nilai warna yang lebih besar dari tekanan II yaitu 153 TCU. Analisis BOD sebelum penyaringan 2,43 mg/l menjadi 1,86 mg/l pada tekanan I. Total suspended solid sebelum penyaringan sebesar 39,7 mg/L mengalami penurunan kadar TSS pada tekanan I sebesar 26,79 mg/L dan tekanan II sebesar 26,40 mg/L. Hasil analisis Minyak dan lemak nilai sebelum penyaringan sebesar 700 µg/L mengalami penurunan setelah dilakukan penyaringan pada tekanan I sebesar 501 µg/L dan tekanan II sebesar 516 µg/L.